Improved estimates of glacier change rates at Nevado Coropuna Ice Cap, Peru - Kochtitzky, William H.; Edwards, Benjamin R.; Enderlin, Ellyn M.; Mariño Salazar, Jersy; Manrique Llerena, Nélida (Cambridge University Press, 2018)
Accurate quantification of rates of glacier mass loss is critical for managing water resources and for assessing hazards at ice-clad volcanoes, especially in arid regions like southern Peru. In these regions, glacier and snow melt are crucial dry season water resources. In order to verify previously reported rates of ice area decline at Nevado Coropuna in Peru, which are anomalously rapid for tropical glaciers, we measured changes in ice cap area using 259 Landsat images acquired from 1980 to 2014. We find that Coropuna Ice Cap is presently the most extensive ice mass in the tropics, with an area of 44.1 km2, and has been shrinking at an average area loss rate of 0.409 km2 a−1 (~0.71% a−1) since 1980. Our estimated rate of change is considerably lower than previous studies (1.4 km2 a−1 or ~2.43% a−1), but is consistent with other tropical regions, such as the Cordillera Blanca located ~850 km to the NW (~0.68% a−1). Thus, if glacier recession continues at its present rate, our results suggest that Coropuna Ice Cap will likely continue to contribute to water supply for agricultural and domestic uses until ~2120, which is nearly 100 years longer than previously predicted.